Determinants of the Long-Term Correlation between Crude Oil and Stock Markets - Lu Yang; Lei Yang; Kung-Cheng Ho; Shigeyuki Hamori (Energies, 2019)
This study employed a dynamic conditional correlation−mixed-data sampling (DCC−MIDAS) approach and panel data analysis to examine the factors that influence the long-term correlation between crude oil and stock markets. Our study shows that there is a positive long-term conditional correlation between oil prices and stock markets, except during the 2008 global financial crisis and the 2011 European debt crisis. We also found that macroeconomic factors have a significant impact on this correlation. Specifically, risk-free rate has a positive effect, whereas economic activity and credit risk has a negative effect. Our results provide useful information for investors and monetary authorities.